THE PHENOMENON OF CHEATING AMONG ELEMENTARY SCHOOL STUDENTS - Daviq Chairilsyah (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
Cheating on elementary school students has occurred for a long time, but it is still difficult for teachers and schools to overcome this phenomenon. Cheating causes children to be dishonest in achieving high scores. Besides, cheating will also have an impact when the students become adults. This behavior is harmful to other students who have studied hard and been honest in completing exams and assignments from teachers at school. Cheating is an act that is dishonest, fraudulent, and justifies any means to obtain a high score in completing tasks, especially on tests or exams. This article applied a literature review as the research methodology to explain situational, dispositional, personal, and external factors causing cheating. It was observed that cheating mostly done by students included changing answers in the exam after reading notes when the teacher was out of the classroom, using notes prepared to answer the questions, looking at or asking for answers from other students, and allowing other students to view or copy their answers. This article encouraged the participation of parents, classroom teachers, and school institutions to work together to improve the students’ self-awareness so that cheating would not become a habit to reach a high score in the future.